Chronic inflammation‐elicited liver progenitor cell conversion to liver cancer stem cell with clinical significance. Issue 6 (6th November 2017) - Li, Xiao‐Feng; Chen, Cheng; Xiang, Dai‐Min; Qu, Le; Sun, Wen; Lu, Xin‐Yuan; Zhou, Teng‐Fei; Chen, Shu‐Zhen; Ning, Bei‐Fang; Cheng, Zhuo; Xia, Ming‐Yang; Shen, Wei‐Feng; et al.
Abstract : The substantial heterogeneity and hierarchical organization in liver cancer support the theory of liver cancer stem cells (LCSCs). However, the relationship between chronic hepatic inflammation and LCSC generation remains obscure. Here, we observed a close correlation between aggravated inflammation and liver progenitor cell (LPC) propagation in the cirrhotic liver of rats exposed to diethylnitrosamine. LPCs isolated from the rat cirrhotic liver initiated subcutaneous liver cancers in nonobese diabetic/severe combined immunodeficient mice, suggesting the malignant transformation of LPCs toward LCSCs. Interestingly, depletion of Kupffer cells in vivo attenuated the LCSC properties of transformed LPCs and suppressed cytokeratin 19/Oval cell 6–positive tumor occurrence. Conversely, LPCs cocultured with macrophages exhibited enhanced LCSC properties. We further demonstrated that macrophage‐secreted tumor necrosis factor‐α triggered chromosomal instability in LPCs through the deregulation of ubiquitin D and checkpoint kinase 2 and enhanced the self‐renewal of LPCs through the tumor necrosis factor receptor 1/Src/signal transducer and activator of transcription 3 pathway, which synergistically contributed to the conversion of LPCs to LCSCs. Clinical investigation revealed that cytokeratin 19/Oval cell 6–positive liver cancer patients displayed a worse prognosis and exhibited superior response to sorafenib treatment. Conclusion: Our results not only clarify the cellular and molecular mechanisms underlying the inflammation‐mediated LCSC generation but also provide a molecular classification for the individualized treatment of liver cancer. (Hepatology 2017;66:1934–1951)